1995
DOI: 10.1073/pnas.92.21.9791
|View full text |Cite|
|
Sign up to set email alerts
|

Antibody-targeted superantigens are potent inducers of tumor-infiltrating T lymphocytes in vivo.

Abstract: Recruitment of antigen-specific tumor-infiltrating lymphocytes (TILs) is a major goal for immunotherapy of malignant tumours. We now describe that T-cell-activating superantigens targeted to a tumor by monoclonal antibodies induced large numbers of pseudospecific TILs and eradication of micrometastases. As a model for tumor micrometastases, syngeneic B16 melanoma cells transfected with the human colon carcinoma antigen C215 were injected intravenously into C57BL/6 mice and therapy with an anti-C215 Fab fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 16 publications
0
48
0
Order By: Relevance
“…Targeting of superantigens has previously been described for colon cancer therapy (Dohlsten et al, 1994(Dohlsten et al, , 1995b. This therapy leads to infiltration of T-cells in the tumour tissue (Dohlsten et al, 1995a, Litton et al, 1996. Superantigen therapy stimulates both CD4+ and CD8+ T-cells (Dohlsten et al, 1995a) that have potent cytotoxic properties to directly kill target cells, but secondary effects such as cytokine secretion and recruitment of other effector cells may be of even higher importance for successful therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeting of superantigens has previously been described for colon cancer therapy (Dohlsten et al, 1994(Dohlsten et al, , 1995b. This therapy leads to infiltration of T-cells in the tumour tissue (Dohlsten et al, 1995a, Litton et al, 1996. Superantigen therapy stimulates both CD4+ and CD8+ T-cells (Dohlsten et al, 1995a) that have potent cytotoxic properties to directly kill target cells, but secondary effects such as cytokine secretion and recruitment of other effector cells may be of even higher importance for successful therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This therapy leads to infiltration of T-cells in the tumour tissue (Dohlsten et al, 1995a, Litton et al, 1996. Superantigen therapy stimulates both CD4+ and CD8+ T-cells (Dohlsten et al, 1995a) that have potent cytotoxic properties to directly kill target cells, but secondary effects such as cytokine secretion and recruitment of other effector cells may be of even higher importance for successful therapy. These secondary events are important to kill sub-populations of cancer cells not expressing the antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAg have, in contrast to conventional peptide antigens, a unique capacity of activating both subsets of Tcells (Herrmann et al, 1990;Dohlsten et al, 1990). In fact, it has been demonstrated previously that both CD4 + and CD8 + T-cells are recruited to the tumour area in response to antibody-targeted SAg tumour therapy (Dohlsten et al, 1995a;Litton et al, 1996Litton et al, , 1997Rosendahl et al, 1998a). However, both subsets have the potential to regulate helper activity as well as cytotoxic functions.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that IFN-γ-producing tumour-infiltrating lymphocytes (TIL) infiltrate the tumour area in immunocompetent animals given four repeated injections of Fab-SEA (Dohlsten et al, 1995a). In order to determine which T-cell subset was required to obtain maximal infiltration of TIL, CD4 KO and CD8 KO mice were treated with Fab-SEA, and the cell infiltration as well as the IFN-γ production was monitored.…”
Section: The Functional Importance Of Cd4 + T-cellsmentioning
confidence: 99%